Dual-task and electrophysiological markers of executive cognitive processing in older adult gait and fall-risk - Walshe, Elizabeth A.; Patterson, Matthew R.; Commins, Seán; Roche, Richard A. P. (Frontiers in Human Neuroscience, 2015)
The role of cognition is becoming increasingly central to our understanding of the complexity of walking gait. Here, we report two experiments which investigated the cognitive and neural processes underlying older adult gait and fall-risk. Experiment 1 employed a dual-task paradigm in young and older adults, to assess the relative effects of higher-level executive function tasks (n-Back, Serial Subtraction and visuo-spatial Clock task) in comparison to non-executive distracter tasks (motor response task and alphabet recitation) on gait. All dual-tasks elicited changes in gait for both young and older adults, relative to baseline walking. Significantly greater dual-task costs were observed for the executive tasks in the older adult group, as hypothesized. Experiment 2 compared normal walking gait, seated cognitive performances and concurrent event-related brain potentials (ERPs) in healthy young and older adults, to older adult fallers. No significant differences in cognitive performances were found between fallers and non-fallers. However, a clear P3a peak was evident on the Stroop task for older non-fallers, which was notably absent in older fallers. This may be indicative of the presence of some cortically-based compensatory process in this group, contributing to their reduced risk of falling. We argue that executive functions play a prominent role in walking and gait, but the role of higher cognition as a predictor of fall-risk needs further investigation.